Photoluminescence Properties of Two Closely Related Isostructural Series Based on Anderson-Evans Cluster Coordinated With Lanthanides [Ln(H2O)7{X(OH)6Mo6O18}]•yH2O, X = Al, Cr - Tewari, Shailabh; Adnan, Mohammad; Balendra,; Kumar, Vineet; Jangra, Gaurav; Prakash, Gaddam Vijaya; Ramanan, Arunachalam (Frontiers in Chemistry, 2019)
The paper describes synthesis and structural characterization of the whole series of two closely related lanthanide coordinated chromium or aluminum hexamolybdates (Anderson-Evans cluster) including twelve new members hitherto unreported: [Ln(H2O)7{X(OH)6Mo6O18}]·4H2O and [Ln(H2O)7{X(OH)6Mo6O18}Ln(H2O)7]{X(OH)6Mo6O18}·16H2O where X = Al or Cr and Ln = La, Ce, Pr, Nd, Sm, Eu, Gd, Tb, Dy, Ho, Er, Tm, Yb, Lu, and Y. Crystal structures of all the solids were established by powder and single crystal X-ray diffraction techniques. The two series are dictated by a different aggregation of the same set of molecular species: Lighter lanthanides favor coordination interaction between lanthanide ions and molybdate cluster forming 1D chains (Series I) while the heavier lanthanides result in the stacking of a cation, a pair of lanthanide hydrates coordinating to the cluster, and an anion, the discrete cluster is further stabilized through a large number of water molecules (Series II). Crystallization with Er3+ and Tm3+ ions results in a concomitant mixture of Series I and II. Photoluminescence of single crystals of all the chromium molybdates was dominated by a ruby-like emission including those which contain optically active ions Pr, Sm, Eu, Tb, Dy, and Tm. In contrast, aluminum analogs showed photoluminescence corresponding to characteristic lanthanide emissions. Our results strongly suggest a possible energy transfer from f levels of lanthanide ions to d levels of chromium (III) causing the quenching of lanthanide emission when coordinated with chromium molybdates. Intensity measurements showed that the emission from chromium molybdates are almost two orders of magnitude lower than naturally occurring ruby with broader line widths at room temperature.